Prognostic relevance of exercise pulmonary hypertension for new-onset atrial fibrillation in primary mitral regurgitation. (25th November 2020) - Teramoto, K; Izumo, M; Kuwata, S; Kamijima, R; Suzuki, T; Nishikawa, H; Mizukoshi, K; Takai, M; Ohara, H; Harada, T; Akashi, Y.J
Abstract: Background/Introduction: New-onset of atrial fibrillation (AF) portends poor prognosis in patients with primary mitral regurgitation (MR). However less is known about prognostic indicator for new-onset AF. Purpose: The purpose of this study was to identify the prognostic relevance of exercise pulmonary hypertension for the new-onset AF in patients with primary MR. Methods: Total of 114 consecutive patients with primary MR who underwent symptom-limited exercise echocardiography using supine-cycle ergometer were followed for new-onset AF over mean follow-up time of 3.6±2.6 years. Those with prevalent AF and pulmonary hypertension (estimated systolic pulmonary artery pressure ≥50mmHg) prior to exercise echocardiography were excluded from our analysis. We defined exercise-induced pulmonary hypertension (ExPHT) as those with peak estimated systolic pulmonary artery pressure (SPAP) ≥60mmHg or delta SPAP defined as differences between rest and peak SPAP ≥20mmHg. Results: The mean age was 61±15 years old and 70 (61%) were male. Of those, 8 (7.8%) had mild MR, 32 (31.1%) had moderate MR, and 63 (61.2%) had severe MR. 60 (52.2%) patients had ExPHT. A total of 27 cases of new-onset AF were found during follow-up where the ExPHT group had higher prevalence of new-onset AF than the non-ExPHT group (35% vs. 11%, p=0.002). Those with ExPHT had significantly stronger association with shorter event-free survival time of new-onset AF (log-rank p<0.001, Figure). When adjusted for age, sex, body surface area, the American Society of Echocardiography MR grade, left atrial dimension, peak systolic blood pressure and heart rate, the multivariable Cox regression analysis showed that those with ExPHT had a hazard risk of 3.1 ([95% CI 1.1–9.1], p=0.039) for new-onset of AF. Conclusions: Exercise-induced pulmonary hypertension predicted incident of new-onset AF in those with primary MR. Exercise echocardiography is expected to play an important role in decision making with regards to the optimal timing for surgical intervention in primary MR. Funding Acknowledgement: Type of funding source: None